Staging of immuno-virological dynamics during acute HIV infection in a Belgian prospective cohort study - Jozefien De Clercq; Marie-Angélique De Scheerder; Sophie Vanherrewege; Els Caluwé; Nathalie Moreels; Danny Delooze; Annemieke Dhondt; Marc Coppens; Stefaan J. Vandecasteele; Sabine D. Allard; Coca Necsoi; Stéphane De Wit; et al. (Elsevier, 2024)
Background: The events during acute HIV infection (AHI) set the stage for the subsequent course of the disease. Early initiation of antiretroviral therapy (ART) has been associated with favorable immunovirological outcomes, yet the precise impact of ART timing during AHI remains unclear, particularly on lymphoid tissues. Materials and methods: The ACS cohort is a prospective cohort study in Belgium, collecting longitudinal clinical data and human bodily material (HBM) from people diagnosed and treated during AHI. The aim of the cohort is to study the impact of ART initiation during AHI on HIV reservoir and immune dysfunction in peripheral blood and anatomical sanctuary sites, as well as its effect on the gut microbiome. The cohort consists of two HBM sampling trajectories: one limited (blood, stool and leukapheresis) and a more extensive one (blood, stool, leukapheresis, colonoscopy, inguinal lymph node excision and lumbar puncture). Here we describe the baseline characteristics, immunovirological outcomes, safety and tolerability of HBM sampling. Results: Between March 2016 and April 2024, 47 participants were enrolled, predominantly men who have sex with men (MSM), with a median age of 36 years [IQR 30-43.5]. Almost 90 % of participants initiated ART within 72 h after study inclusion, irrespective of HBM sampling trajectory. The timing of ART initiation according to the Fiebig stage did not significantly impact immune recovery (CD4/CD8 ratio ≥1) or the time to viral suppression. Approximately 40 % of participants opted for the extensive HBM sampling trajectory during AHI. However, the participation rate for the extensive trajectory decreased by nearly half at the longitudinal follow-up timepoint. In general, study-related procedures were safe and well-tolerated, with limited procedure-related adverse events (AEs). Inguinal lymph node excision was associated with the highest AE rate, in line with previous reports. Conclusions: Our findings reaffirm the beneficial effect of ART initiation during AHI on long term immunovirological outcomes, regardless of Fiebig stage at treatment initiation. Additionally, we demonstrate that the collection of HBM during and longitudinally after AHI is safe and feasible, without compromising time to ART initiation. Cohorts that integrate comprehensive clinical data with high-quality HBM samples are essential to longitudinally study the impact of early ART on reservoir dynamics and immune responses across various anatomical sites after AHI.